A high-order finite element model for vibration analysis of cross-laminated timber assemblies. Issue 3 (September 2017) - Paolini, Alexander; Kollmannsberger, Stefan; Winter, Christoph; Buchschmid, Martin; Müller, Gerhard; Rabold, Andreas; Mecking, Simon; Schanda, Ulrich; Rank, Ernst
The vibration behavior of cross-laminated timber components in the low-frequency range can be predicted with high accuracy by the finite element method. However, the modeling of assembled cross-laminated timber components has been studied only scarcely. The three-dimensional p-version of the finite element method, which is characterized by hierarchic high-order shape functions, is well suited to consider coupling and support conditions. Furthermore, a small number of degrees of freedom can be obtained in case of thin-walled structures using p-elements with high aspect ratios and anisotropic ansatz spaces. In this article, a model for cross-laminated timber assemblies made of volumetric high-order finite elements is presented. Two representative types of connections are investigated, one with an elastomer between the cross-laminated timber components and the other without. The model is validated, and suitable ranges for the stiffness parameters of the finite elements which represent the junctions are identified.